The effects of trade liberalization on household poverty in South African between 1996 and 2001 - Sibanda, Andile (School of Economics, 2022)
Since South Africa entered the international markets and opened its borders to international trade, the economy has undergone a gradual process of trade reforms ensuring that the South African economy becomes competitive. It is recognized globally that trade liberalization is a key factor to enhancing economic welfare, trade, and efficiency. Trade liberalization aims to reduce import protection and enable easy flow of resources from sectors that are less competitive to sectors with a comparative advantage. Hence, trade liberalization is believed to play an important role in spurring growth and improving household welfare through various channels. This study analyses the impact of South Africa's trade liberalization on household poverty between 1996 and 2001 at a local level using regional level indicators of trade exposure. The study uses household income as a proxy for household poverty. The results using the simple OLS estimator leads to some interesting findings. We find that there is a positive relationship between household income and sectorial weighted average tariff in region, that is, trade liberalization led to a reduction in household income in the region. We also find that increased exposure to tariff reductions translates to an increase in the number of individuals employed in a household. However, this does not appear to be the case with employment in the manufacturing sector. We find that tariffs reductions reduced employment opportunities in the manufacturing sector, leading to reductions in individuals employed in the manufacturing sector. Lastly, we find that household income of households that have a high share of family in the manufacturing sector are negatively affected by tariff exposure. These results illustrate structural changes in response to tariff liberalization led to varied impacts across households and regions in South Africa.